Mediated effect of project management asset characteristics on firm performance. Issue 7 (21st June 2019) - Jugdev, Kam; Mathur, Gita; Fung, Tak
Abstract : Purpose: The purpose of this paper is to study how project-level performance mediates the effect of project management assets on firm-level performance by examining the direct and mediated relationships between the project management process characteristics: valuable, rare, inimitable and organizationally supported on project-level and firm-level performance outcomes. Design/methodology/approach: This paper analyzes data from an online survey completed by 198 North American Project Management Institute® members. Linear regression and Sobel Tests are used to examine the relationships between nine factors extracted from an exploratory factor analysis that comprise project management asset characteristics, one factor that comprises project-level performance outcomes, and one factor that comprises firm-level performance outcomes. Findings: Not only does project-level performance positively and significantly affect firm-level performance, but project-level performance also significantly mediates the effect of project management asset characteristics (for all nine factors) on firm performance. Research limitations/implications: Limitations of this study include sample size and self-report bias, calling for a larger sample in ongoing research. Practical implications: This study contributes to the stream of literature on project management assets as sources of competitive advantage and makes the case for sustained organizational investments in the project management process. Originality/value: This paper contributes to the limited, but increasing interest in applying the resource-based view of the firm to project management capabilities as a source of competitive advantage.